VD_FINDINFO AP / 2010 / 60 vom 24. September 2009 - VD Tribunal cantonal (2009)
DOUTE, APPRÉCIATION DES PREUVES, DROIT D'ÊTRE ENTENDU, RECOURS EN ANNULATION | 370 al. 1 CPP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP